Case report: an unwanted leftover after laparoscopic cholecystectomy. Issue 3 (4th May 2018) - Stroobants, Eline; Cools, Peter; Somville, Francis
Abstract: Background: A 72-year-old female patient with a history of laparoscopic cholecystectomy presented at the gastroenterology consultation with intermittent complaints of abdominal pain since two months in the right hemi abdomen. Methods: Imaging discovered a subhepatic abscess. Explorative surgery showed multiple gallstones as the cause of the abscess. A brief literature study was conducted and after a thorough selection based on title and abstract, we ended up with 14 articles. These were compared in the discussion with the literature concerning incidence, range of complications, risk factors and prevention and management. Results: Spilled gallstones are an unusual complication of a frequently performed procedure. Conclusions: This case report elaborates on the incidence, different complications, prevention and management of spilled gallstones by means of a brief literature study. In case spillage happens removal of as many gallstones as possible is indicated the spillage should also be communicated to the patient to ease the diagnosis of a possible complication.